Improvements and alternatives to intellectual property: a survey - Nomoto, Marcelo Yuji (2007)
An important share of the economic growth is due to innovations. This thesis reviews the recent literature in intellectual property. This survey discusses the following papers: Kremer (1998), Boldrin and Levine (2001), Kremer (2001), Shavell and Ypersele (2001), Lerner (2002) and DiMasi, Hansen, and Grabowski (2003). These include both empirical and theoretical articles. In the fírst category, there is one study about the responses in innovation caused by a change in patenfs strength and another about the cost of developing new drugs. The theoretical studies propose enhancements and alternatives to the patent system, e.g. optional rewards, patent buyouts, elimination of patents in some sectors and advanced purchase commitments.